1994
DOI: 10.1085/jgp.104.1.123
|View full text |Cite
|
Sign up to set email alerts
|

ATP alters current fluctuations of cystic fibrosis transmembrane conductance regulator: evidence for a three-state activation mechanism.

Abstract: The cystic fibrosis gene product cystic fibrosis transmembrane conductance regulator (CFTR) is a low conductance, cAMP-regulated C1-channel. Removal of cytosolic ATP causes a cessation of cAMP-dependent kinase-phosphorylated CFTR channel activity that resumes upon ATP addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
94
3

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(113 citation statements)
references
References 66 publications
16
94
3
Order By: Relevance
“…Additionally, kinetic behavior of the channels in control conditions (see Figs. 4 and 5) was indistinguishable from our previous characterization of CFTR when evaluated in this system (21,22).…”
Section: Methodscontrasting
confidence: 53%
See 1 more Smart Citation
“…Additionally, kinetic behavior of the channels in control conditions (see Figs. 4 and 5) was indistinguishable from our previous characterization of CFTR when evaluated in this system (21,22).…”
Section: Methodscontrasting
confidence: 53%
“…To determine the mechanism of this inhibition, the effect of ibuprofen on CFTR Cl Ϫ channels in excised, inside-out patches from mouse L cells recombinantly expressing CFTR (19) was determined. We characterized previously the kinetics of nucleotide-dependent gating (21,22) and sulfonylurea-dependent block of CFTR (23,31) in these cells in detail. The results of one experiment with ibuprofen are shown in Fig.…”
Section: Effect Of Ibuprofen On Cftr In Excised Inside-out Patchesmentioning
confidence: 99%
“…CFTR channels require ATP and cAMP to open. In oocytes, resting ATP levels are sufficient (29,30); however, cAMP levels need to increase, and experimentally this can be accomplished by adding extracellular forskolin to stimulate adenylyl cylase activity. Fig.…”
Section: Site-directed Editase Can Specifically Correct a Premature Tmentioning
confidence: 99%
“…Most ABC proteins are presumed to hydrolyze ATP in transporting solutes across the cell membrane as has been demonstrated for the periplasmic permeases (Hyde et al, 1990;Ames and Lecar, 1992). However, CFTR is a chloride channel which requires both PKAdependent phosphorylation to initiate activity and the continued presence of ATP for steady state channel gating (Anderson, Berger, Rich, Gregory, Smith, and Welsh, 1991;Nagel, Hwang, Nastiuk, Nairn, and Gadsby, 1992;Venglarik, Schultz, Frizzell, and Bridges, 1994; see reviews by Anderson, Sheppard, Berger, and Welsh, 1992;Collins, 1992). It has been suggested that CFTR hydrolyzes ATP as a necessary step in channel gating.…”
Section: Introductionmentioning
confidence: 99%
“…More complex schemes have been proposed which include nucleotide binding at both putative NBDs with hydrolysis occurring at the first NBD , the second NBD , or both NBDs, but with one hydrolytic event leading to channel opening and the second hydrolytic event leading to channel closure (Baukrowitz, Hwang, Nairn, and Gadsby, 1994;Hwang, Nagel, Nairn, and Gadsby, 1994). We (Venglarik et al, 1994) proposed a scheme to account for details of the gating properties seen at 37~ that is an extension of that proposed by Winter, Sheppard, Carson, and Welsh (1994). The kinetic scheme presented as Scheme I, requires the presence of ATP for channel gating to occur, but neither requires nor precludes ATP hydrolysis as a step in this gating.…”
Section: Introductionmentioning
confidence: 99%